Developing Human Resource Competitiveness in The Sharia Rural Bank Industry Based on Positioning Strategy - Arif Julianto Sri Nugroho; Tasari Tasari; Anna Febrianty Setianingtyas; Dandang Setyawanti; Ummu Hany Almasitoh; Rizky Windar Amelia (Goodwood Publishing, 2026)
Purpose: This study explores the competitive excellence of human resources in Islamic Rural Banks (BPR Syariah) in the Soloraya region. It aims to identify marketing strategies to enhance public trust and satisfaction with the services provided by these banks in the industry 4.0 era, addressing the